RADIATION ENHANCED MICRO CRACKING AND POROUS FORMATION IN DOPED GLASSY POLYMERS (Baghdad Science Journal, 2025)
Glassy polymers like Poly Mathyel Metha Acrylate are usually classified as non-porous materials; they are almost considered as fully transparent. Thin samples of these materials reflect color changing followed by porous formation and consequently cracking when exposed to certain level of ?-irradiation. The more the dose is the higher the effect have been observed. The optical microscope and UV-VIS spectroscopy have clearly approved these consequences especially for doped polymers.